Loss of expression and promoter methylation of SLIT2 are associated with sessile serrated adenoma formation. - Andrew D Beggs; Angela Jones; Neil Shepherd; Abed Arnaout; Caroline Finlayson; A Muti Abulafi; Dion G Morton; Glenn M Matthews; Shirley V Hodgson; Ian P M Tomlinson (PLoS Genetics)
Serrated adenomas form a distinct subtype of colorectal pre-malignant lesions that may progress to malignancy along a different molecular pathway than the conventional adenoma-carcinoma pathway. Previous studies have hypothesised that BRAF mutation and promoter hypermethylation plays a role, but the evidence for this is not robust. We aimed to carry out a whole-genome loss of heterozygosity analysis, followed by targeted promoter methylation and expression analysis to identify potential pathways in serrated adenomas. An initial panel of 9 sessile serrated adenomas (SSA) and one TSA were analysed using Illumina Goldengate HumanLinkage panel arrays to ascertain regions of loss of heterozygosity. This was verified via molecular inversion probe analysis and microsatellite analysis of a further 32 samples. Methylation analysis of genes of interest was carried out using methylation specific PCR (verified by pyrosequencing) and immunohistochemistry used to correlate loss of expression of genes of interest. All experiments used adenoma samples and normal tissue samples as control. SSA samples were found on whole-genome analysis to have consistent loss of heterozygosity at 4p15.1-4p15.31, which was not found in the sole TSA, adenomas, or normal tissues. Genes of interest in this region were PDCH7 and SLIT2, and combined MSP/IHC analysis of these genes revealed significant loss of SLIT2 expression associated with promoter methylation of SLIT2. Loss of expression of SLIT2 by promoter hypermethylation and loss of heterozygosity events is significantly associated with serrated adenoma development, and SLIT2 may represent a epimutated tumour suppressor gene according to the Knudson "two hit" hypothesis.